Optimization of Xylose Production from Sugarcane Trash by Microwave-Maleic Acid Hydrolysis - Euis Hermiati; Maulida Oktaviani; Riksfardini Annisa Ermawar; Raden Permana Budi Laksana; Lutfi Nia Kholida; Ahmad Thontowi; Siti Mardiana; Takashi Watanabe (Dept. of Chemical Engineering, Diponegoro University, 2020)
Sugarcane trash contains significant amount of xylan that could be hydrolysed to xylose. The xylose could be further fermented to produce xylitol, a sugar alcohol that has low calories and does not cause carries of teeth. In this study we optimized the production of xylose from sugarcane trash by microwave-assisted maleic acid hydrolysis using response surface methodology (RSM). The factors optimized were acid concentration, time, and temperature. The xylose yield based on the weight of initial biomass was determined and it served as a response variable. Results show that acid concentration and interaction between time and temperature had significant effect on xylose yield. The quadratic regression model generated from the optimization was fit and can be used to predict the xylose yield after hydrolysis with various combinations of acid concentration, time, and temperature. The optimum condition for xylose production from sugarcane trash was using maleic acid of 1.52%, and heating at 176 °C for 6.8 min. At this condition the yield of xylose was 24.3% per initial biomass or 0.243 g/ g biomass.Keywords: maleic acid; microwave heating; response surface methodology; sugarcane trash, xylose